Anastomotic leaks can be detected within 5 days following ileorectal anastomosis: a case‐controlled study in patients with familial adenomatous polyposis. (March 2017) - Aziz, O.; Albeyati, A.; Derias, M.; Varsani, N.; Ashrafian, H.; Athanasiou, T.; Clark, S. K.; Jenkins, J. T.; Kennedy, R. H.
Abstract: Aim: To determine the earliest time point at which anastomotic leaks can be detected in patients undergoing total colectomy with primary ileorectal anastomosis for familial adenomatous polyposis. Method: This was a case‐controlled study of 10 anastomotic leak patients vs 20 controls following laparoscopic total colectomy with ileorectal anastomosis for familial adenomatous polyposis (from 96 consecutive patients between 2006 and 2013). Panel time‐series data regression was performed using a double subscript structure to include both variables. A generalized least squares multivariate approach was applied in a random effects setting to calculate correlations for observations, with anastomotic leak being the dependent variable. Univariate and multivariate regression calculations were then performed according to individual observations at each recorded time point. Time‐series analysis was used to determine when a variable became significant in the leak group. Results: Multivariate analysis identified a significant difference between leak and control groups in mean heart rate ( P  <   0.001), mean respiratory rate ( P  =   0.017) and mean urine output ( P  =   0.001). Time‐point analysis showed that heart rate was significantly different between leak and control groups at postoperative day 4.25. Multivariate analysis identified a significant difference between groups in alanine transaminase ( P  =   0.006), bilirubin ( P  =   0.008), creatinine ( P  = 0.001), haemoglobin ( P  <   0.001) and urea ( P  =   0.007). There were no differences between groups with regard to markers of inflammation such as albumin, white blood cell count, neutrophil count and C‐reactive protein. Conclusion: Anastomotic leaks can be detected early (within 4.5 days of surgery) through changes in physiological, blood test and observational parameters, providing an opportunity for early intervention in these patients to salvage the anastomosis.